2017
DOI: 10.1007/s00705-017-3504-0
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic distribution and tissue tropism of avian encephalomyelitis virus isolate XY/Q-1410 in experimentally infected Korean quail

Abstract: Avian encephalomyelitis (AE) is an important infectious poultry disease worldwide that is caused by avian encephalomyelitis virus (AEV). However, to date, the dynamic distribution of AEV in quails has not been well described. Quantitative real-time polymerase chain reaction (qPCR) and immunohistochemistry (IHC) assays were used to investigate the dynamic distribution and tissue tropism of AEV in experimentally infected Korean quail. AEV was detected in the cerebrum, cerebellum, proventriculus, intestine, liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…High expression of lncRNA CCHE1 has been reported to be an indicator of poor prognosis in CC 14 . In addition, overexpression of lncRNA Hox transcript antisense intergenic RNA (HOTAIR) has been strongly linked with the progression of CC 15 . More recently, mounting evidence has indicated that knockdown of lncRNAs negatively regulates CC cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High expression of lncRNA CCHE1 has been reported to be an indicator of poor prognosis in CC 14 . In addition, overexpression of lncRNA Hox transcript antisense intergenic RNA (HOTAIR) has been strongly linked with the progression of CC 15 . More recently, mounting evidence has indicated that knockdown of lncRNAs negatively regulates CC cells.…”
Section: Discussionmentioning
confidence: 99%
“…The sections were then mounted with neutral resin and finally viewed and imaged under a microscope. IHC scoring was performed using Image-Pro Plus 7 software (Media Cybernetics) 15 , 16 . The staining intensity was scored as follows: 0 (negative), 1 (weak), 2 (moderate), and 3 (strong).…”
Section: Methodsmentioning
confidence: 99%
“…The entry and propagation of virus into cells can induce a variety of cytopathic effects (CPEs). The typical CPE caused by membrane fusion of velogenic and mesogenic NDV or proteasetreated lentogenic strains in susceptible cells is syncytium formation (Fan et al, 2017;Wang et al, 2017). Then the syncytia died and were exfoliated to produce plaques on cell monolayers.…”
Section: Introductionmentioning
confidence: 99%
“…The AEV strain XY/Q-1410 (GenBank accession no. NC_003990) ( Fan et al., 2017 ), the PPMV-1 strain GS02 isolate (GenBank accession no. OM640464) ( Zhang et al., 2022 ), the FAdV-4 strain SXD15 ( Wang et al., 2018 ), and the IBV strain CK/CH/Shaanxi/2009/H09 (GenBank accession no.…”
Section: Methodsmentioning
confidence: 99%
“…A melting curve analysis was used to evaluate the amplification result. The standard curve of AEV VP1 gene, PPMV-1 NP gene, MDV Meq, FADV-4 hexon gene, IBV N gene were established previously ( Fan et al., 2017 ; Yu et al., 2018 ; Wang et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%